PENGEMBANGAN INSTRUMEN EVALUASI PILIHAN GANDA BERBASIS HOTS PADA MATA PELAJARAN PAIBP - Lailatul Muniroh; Muhammad Kris Yuan Hidayatulloh (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
The ability of students to be able to think to a higher level (Higher Order Thinking Skills / HOTS) is very necessary in learning in this era. Educators are required to be able to develop test questions or assessment items that can trigger students to have the ability to think at a higher level. The purpose of this study is to develop an evaluation instrument in the form of multiple choice question based on Higher Order Thinking Skills (HOTS), test the feasibility level of HOTS based multiple choice evaluation instruments that have been develop, analyze student HOTS and analyze student responses to the use of multiple choice evaluation instruments. The method used in this research is the development research method or commonly referred to as Research & Development with a development model developed by Dick. W., Carey L., and Carey J.O by going through the stages of ADDIE (Analysis, Design, Development, Evaluation). Five stages that are very useful in the development step. The subjects in this study were 30 students of grade V SD Negeri Kepanjen 2 Jombang. The results of product validation development from three expert validators obtained an average validation value of 86.64% (very valid). As for the results of the development, showing that of the 20 questions developed, 16 questions are feasible based on the calculation of r calculate > r table, which is 0,3061.The reliability of the questions is 1.00 > 0.737 so that it gets a reliable predicate. The difficulty level of the question has an average score of 0.6215 which means "medium". With a composition of 1 very difficult question, 1 difficult question, 8 medium questions, 7 easy questions and 3 very easy questions. The results showed positive values which showed that the number of students in the upper group answered more correctly on the questions given, and the number of students in the lower group answered more incorrectly on the questions given. Trials on this study showed "moderate" results on his higher-order thinking skills. Student responses have an average value of 7.72%, which means that they get a positive response in the use of HOTS-based multiple-choice question development instruments when applying these instruments.So it can be concluded that the evaluation instrument developed is suitable for use in learning.